Field experiments on individual adaptation of the spider crab Inachus phalangium to its sea anemone host Anemonia viridis in the northern Adriatic Sea - LANDMANN, S.; MEYER, R.; BOETTCHER, A.; PFANNKUCHEN, M.; MELZER, R. (Mediterranean Marine Science, 2015)
We studied the adaptation of the spider crab Inachus phalangium (Fabricius, 1755) to one of its sea anemone host species, Anemonia viridis (Forsskål, 1775) in the coastal region of Rovinj, Croatia. Similar to other brachyuran species, Inachus spp. generally lives within the anemone to obtain protection from possible predators. Using removal and reintroduction experiments, this study investigates the protection mechanism and shows a loss of adaptation after a period of 10 days when the crabs are taken out of their host and kept solitary. Thirty-nine anemones from two different trial sites were marked individually and the inhabiting crabs were isolated to be released back into their individual hosts later. The reactions of the anemones were closely observed and characterized to determine the respective state of crab adaptation. As 35 out of 39 individuals provoked a defense /attack reaction of the anemone, it is concluded that the crabs possessed some sort of non-permanent protection mechanism that was lost during the test run (chi-square test, p < 0.00014). All tested crabs re-inhabited their host anemones within a maximum of 20 minutes after they had been reintroduced and stung by the anemones. Therefore, habituation to the host’s defense / attack mechanism is acquired individually and not genetically inherent to the species. The results are compared to adaptation and protection data on other decapod crustaceans and some anemonefishes.